Looking east, looking west: Penang as a knowledge hub - Solvay Gerke; Hans-Dieter Evers (University of Bonn, Center for Development Research (ZEF), 2012)
Penang has always been a focal point, absorbing knowledge (and popular culture) from civilizations to the East and West. In modern Penang the pattern of cultural contacts has changed over time. Research institutes and universities in Penang cooperate with foreign partners to produce research papers and reports. Based on an analysis of joint research output, the changing international position of Penang as an emerging research hub will be analysed. The paper will show that international cooperation has increased considerably between 1970 and 2010, but that there has also been a remarkable shift from European, Australian and American partners to East Asian and to South Asian partners. The latter will be analysed in greater detail to show the development of Penang as an increasingly important Asian knowledge hub. One of the highlighted results of our paper will be the increasing importance of research ties across the Indian Ocean.
Keywords: 330; Science Cooperation; Knowledge Hub; Malaysia